CLINICAL AND PATHOMORPHOLOGICAL EXAMINATION OF MYELOFIBROSIS IN CHRONIC MYELOID LEUKEMIA - T. Yu. Dolgikh; I. V. Kachesov; A. A. Marchenko; N. P. Domnikova (Сибирский онкологический журнал)
Pathomorphology study of marrow fibrosis in patients with chronic myeloid leukemia was carried out using morphometric image analysis software. It was revealed that every second patient had myelofibrosis. The initial and expressed myelofibrosis occur at approximately the same frequency, and their combination is observed more often. Myelofibrosis is more common in the accelerated-phase and blast crisis that in the chronicphase. It was found a direct correlation between the relative area of fibrous tissue in initial and expression myelofibrosis and the number of megakaryocytes, the number of dwarf megakaryocytes in the bone marrow trephine biopsy. The relative area of fibrous tissue in initial and expression myelofibrosis directly correlates with the percentage of blasts in myelogram, the percentage of blasts in the bone marrow trephine biopsy and the percentage of blasts in the peripheral blood in the accelerated phase and blast crisis. The prevalence of both initial and expressed myelofibrosis regardless of the phase of chronic myeloid leukemia directly correlated with the duration of the disease. Expressed myelofibrosis associates with the chemotherapy regardless of the phase of chronic myeloid leukemia. Initial myelofibrosis with the chemotherapy is not connected. Gender and age of the patients are not associated with marrow fibros